Molecular detection of cryptococcus from formalin-fixed paraffin-embedded tissue sample - a noncultural approach for diagnosis of primary pulmonary cryptococcosis - Mohd Rahim, Syarifah; Salleh, Amizatul Aini; Bakrin, Ikmal Hisyam; Tengku Jamaluddin, Tengku Zetty Maztura; Masri, Siti Norbaya (Fakulti Perubatan dan Sains Kesihatan, Universiti Putra Malaysia, 2020)
Despite pulmonary cryptococcosis showing good response to antifungal treatment, making accurate diagnosis in a timely manner remains a challenge. Tissue for fungal culture is less sensitive, nonspecific, and time-consuming to allow for prompt diagnosis. We herein report a case of 31-year-old woman with no known medical illness but presented with history of cough and haemoptysis for two months. The chest X-ray and bronchoscopy revealed left lung mass. While tuberculosis showed negative result and no growth observed in the tissue culture, the histopathological examination (HPE) finding was suggestive of fungal infection. The formalin-fixed paraffin-embedded (FFPE) tissue was sent for molecular testing, which revealed Cryptococcus neoformans. This report emphasises on the advantages and limitations of polymerase chain reaction (PCR) as an alternative method to confirm the diagnosis in cases of culture-negative fungal infection.